Asia-pacific financial market inefficiency: evidence through behavioural models. (10th November 2022) - Zghidi, Nahed
The general equilibrium models with representative agents have proved to be inadequate descriptions of the Asia-Pacific emerging market. Within this framework, we present a model with heterogeneous agents, optimisers, and non-optimisers in which the financial markets consist of agent clusters. Our methodology consists of dividing the market participants into 'rational agents' who form sensible forecasts, and 'irrational agents' who develop biased forecasts, trade on tips, and bid prices away from their fundamental values. The analysis examines monthly frequency stock returns for the Asia-Pacific financial market and world returns using data spanning January 2004 and April 2019. Our results show a positive slope between irrationality and volatility but deterministic for return. Such a persistent connection between irrational and stock volatility suggests that investor sentiment is one of the most crucial determinants of market volatility. The ratio of successful exchange and merger depends on the proportion of the rational agents vs. the irrational ones.